Suppose $gcd(m,n)=1$, and let $F :Z_n→Z_n$ be defined by $F([a])=m[a]$. Prove that $F$ is an automorphism of the additive group $Z_n$. I find it is diffcult to prove $F$ is injective and surjective. Could you please to help me proof it with all the details. I type it roughly, and i am sorry and sincerely looking for a result.

  • 1
    $\begingroup$ Is it clear to you, that the equation $ma=0 \ mod(n)$ has trivial solution? In other words, that $\ker(F) = 0$ and hence the map is injective? An injective endomorphism of a group is automaticaly an isomorphism. $\endgroup$ – Lada Dudnikova Apr 22 at 8:14
  • $\begingroup$ @LadaDudnikova "An injective endomorphism of a group is automatically an isomorphism" - this is not true, see here. $\endgroup$ – Dietrich Burde Apr 22 at 10:48
  • $\begingroup$ @Lada Dudnikova Maybe for the finite group,then "An injective endomorphism of the group to itself is automatically an isomorphism" is true. However, could you please show me that how can i use $gcd(m,n)=1$, and the trivial solution to obtain the map is injective. I am confused about this corollary. $\endgroup$ – B1s Apr 22 at 11:03
  • $\begingroup$ @DietrichBurde sorry, forgot to mention finiteness of the group order here. $\endgroup$ – Lada Dudnikova Apr 22 at 11:03

To show that the map is injective and surjective is equivalent to showing that the map has a two-sided inverse.

The extended Euclidean algorithm yields that there are numbers $m', n'$ such that $$ m m' + n n '= 1. $$ Consider the map $G : Z_{n} \to Z_{n}$ given by $G([b]) = m' [b]$. Then for all $a$ one has $$ G \circ F([a]) = G(F([a])) = G(m [a]) = m'm [a] = (1 - n' n) [a] = [a], $$ as $n [a] = [0]$. Similarly $F \circ G([b]) = [b]$ for all $b$.


I shall prove two things

  1. The solution of $am = 0 \ (mod \ n)$ is trivial
  2. (1) means that the map is injective.

Let there a non-zero element s.t. $am = 0$ modulo $n$. The multiplication by integer in the group means consequtive addition(substraction) of the element to itself. Knowing that $gcd(m,n) = 1$ means that there is such a pair $(x',y')$ that $x'm+y'n = 1 \implies x'm = 1$ modulo $n$

This means $1 = a(x'm) = x'(am) = 0 $ contradiction.

Let the injectivity be violated. Then there is $ma = mb = c \neq 0$ modulo $n$

that means $m(a-b) = c \neq 0$ modulo $n$ which is a contradiction with the previous statement.

I admit that I operate rather dirty making commutative permutations and not justifying why in cyclic group I can do it. Do you need it to be justfied?


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.